Skin, clothing, and dwelling: Max von Pettenkofer, the science of hygiene, and breathing walls - Ekici, Didem (University of California Press, 2016)
Gottfried Semper is often credited with originating the concept of the building as skin in architectural theory, but an alternative trajectory of this idea can be found in the mid-nineteenth-century science of hygiene. In Skin, Clothing, and Dwelling: Max von Pettenkofer, the Science of Hygiene, and Breathing Walls, Didem Ekici explores the affinity of skin, clothing, and dwelling in nineteenth-century German thinking, focusing on a marginal figure in architectural history, physician Max von Pettenkofer (1818–1901), the “father of experimental hygiene.” Pettenkofer’s concept of clothing and dwelling as skins influenced theories of architecture that emphasized the environmental performance of the architectural envelope. This article examines Pettenkofer’s writings and contemporary works on hygiene, ethnology, Kulturgeschichte (cultural history), and linguistics that linked skin, clothing, and dwelling. From nineteenth-century “breathing walls” to today’s high-performance envelopes, theories of the building as a regulating membrane are a testament to the unsung legacy of Pettenkofer and the science of hygiene.